Apology Strategies used by English Major Students at Naresuan University - Katchamart, Pornthep; Cedar, Payung (Chophayom Journal, 2018)
An attempt of this study was to investigate the differences of English apology strategies in various social situations from participants who had differing years of study in order to determine whether or not the number of years of study has an influence on the apology strategies used. The data of this study were elicited from 50 first-year students and 50 third-year students, majoring in English at Naresuan University, Thailand, using a Discourse Completion Test (DCT) The data were categorized based on Olshtain & Cohen (1983) and Blum-Kulka, House & Kasper (1989) apology speech act sets. The findings revealed that the first-year students used a smaller number of categories than the third-year students, and the frequency of use in each category also differed between the two groups of students.